SURVIVAL ANALYSIS OF RECURRENCE AND MORTALITY POST-STROKE AMONG PATIENTS AT CA MAU GENERAL HOSPITAL, 2021–2025 (Vietnam Journal of Community Medicine, 2026)
Objectives: To estimate recurrence-free survival and overall survival after stroke; to compare survival probabilities by stroke subtype; and to identify factors associated with recurrence and mortality.Methods: A retrospective cohort study was conducted on 801 stroke patients treated at Ca Mau General Hospital during 2021–2025. Baseline information was extracted from medical records. Post-discharge recurrence and mortality were ascertained through review of follow-up/readmission records combined with telephone contact with patients or caregivers in 2025. Time zero was defined as the discharge date of the index stroke admission. There were 57 patients lost to follow-up; for these cases, follow-up time was counted until the last date with available information. Treatment adherence was defined as fulfillment of all four criteria: scheduled follow-up visits, regular medication use, home blood pressure monitoring, and dietary adherence. Survival was estimated using the Kaplan–Meier method, compared with the Log-rank test, and associated factors were examined using Cox regression.Results: Among 801 patients, the recurrence rate was 47.19% and the mortality rate was 7.62%. The time at which 25% of patients experienced recurrence was 20.93 months, and the median recurrence time was 58.71 months. For mortality, the 25% and 50% event times could not be estimated because the event rate was low. Log-rank tests showed significant differences in survival by stroke subtype for both recurrence and mortality. Cox regression showed that treatment adherence reduced recurrence risk by 38.7% (HR = 0.61) and mortality risk by 53.6% (HR = 0.46). Moderate-to-severe NIHSS scores and increasing numbers of comorbidities were associated with higher risks of both outcomes; hemorrhagic stroke was also associated with higher mortality.Conclusions: Recurrence was more frequent than mortality during follow-up after stroke. Major factors associated with recurrence and mortality were treatment adherence, stroke severity by NIHSS, comorbidity burden, and stroke subtype.
Keywords: stroke, recurrence, mortality, survival analysis, Kaplan–Meier, Cox regression.